Early osseointegration driven by the surface chemistry and wettability of dental implants - Suelen Cristina SARTORETTO; Adriana Terezinha Neves Novellino ALVES; Rodrigo Figueiredo Britto RESENDE; José CALASANS-MAIA; José Mauro GRANJEIRO; Mônica Diuana CALASANS-MAIA (University of São Paulo, 2015)
Objective The objective of this study was to investigate the impact of two different commercially available dental implants on osseointegration. The surfaces were sandblasting and acid etching (Group 1) and sandblasting and acid etching, then maintained in an isotonic solution of 0.9% sodium chloride (Group 2). Material and Methods X-ray photoelectron spectroscopy (XPS) was employed for surface chemistry analysis. Surface morphology and topography was investigated by scanning electron microscopy (SEM) and confocal microscopy (CM), respectively. Contact angle analysis (CAA) was employed for wetting evaluation. Bone-implant-contact (BIC) and bone area fraction occupied (BAFO) analysis were performed on thin sections (30 μm) 14 and 28 days after the installation of 10 implants from each group (n=20) in rabbits' tibias. Statistical analysis was performed by ANOVA at the 95% level of significance considering implantation time and implant surface as independent variables. Results Group 2 showed 3-fold less carbon on the surface and a markedly enhanced hydrophilicity compared to Group 1 but a similar surface roughness (p>0.05). BIC and BAFO levels in Group 2 at 14 days were similar to those in Group 1 at 28 days. After 28 days of installation, BIC and BAFO measurements of Group 2 were approximately 1.5-fold greater than in Group 1 (p<0.05). Conclusion The surface chemistry and wettability implants of Group 2 accelerate osseointegration and increase the area of the bone-to-implant interface when compared to those of Group 1.